Current Trends and Future Implementation Possibilities of the Merkel Tree - Bosamia, Mansi; Patel, Dharmendra (International Journal of Computer Sciences and Engineering, 2018)
A current popular trend of wallet security research is cryptography. For that Merkle tree is one of the solutions to enhance wallet security. It is basically used for cryptocurrencies, file system authentication, backup system, control system, database, etc. but it can be used for communication authentication and many more. And that is highlighted in this paper by stating the few future Merkle tree implementation possibility with its basic technical requirements. In this survey study also discuss about the Merkle tree concept with its advantages and disadvantages and its implementations such as Bitcoin, Ethereum, Hash-based Cryptography, Apache Cassandra, Btrfs, ZES, IPFS with their comparisons.